Hospitalizations for conditions susceptible to primary care among children and adolescents in Minas Gerais, Brazil, 1999-2007 - Lílian Amaral Santos; Veneza Berenice de Oliveira; Antônio Prates Caldeira
Abstract Objectives: to describe the evolution of rates of Hospitalizations for Conditions Susceptible to Primary Care (HCSPCs) in children and adolescents in Minas Gerais, testing the correlation with population coverage of the Family Health Strategy (FHS). Methods: an ecological study analyzing the evolution over time and correlation with rates of coverage of the FHS between 1999 and 2007. Analyses were carried out for three age groups: 0 - 4 years, 5 - 9 years and 10 - 19 years. Pearson's correlation coefficient was used with a level of significance of 5%. Results: the rates of HCSPAs were found to decline during the period studied. In the population aged 0 - 4 years, a decrease of 19.1% was observed. For the 5 - 9 and 10 - 19 year age groups, the rates fell by 0.6% and 18.5% respectively. There was no significant correlation between the decline in rates and increased FHS coverage. The main causes of hospitalization for all age groups were infectious gastroenteritis, bacterial pneumonia and asthma. Conclusions: despite the decrease observed, the lack of correlation between coverage and rates of HCSPA draws attention to the need for improvement in access to and better professional qualification for child and adolescent healthcare.